The Influence Of Organizational Culture Using The Ocai Approach On The Performance Of Health Personnel At Intan Medika Lamongan Hospital - Lailatul Karimah; Ratna Wardani; Ardi Bastian; Endra Widiyanto (Universitas STRADA Indonesia, 2023)
The performance of health workers is a very important issue in order to maintain and improve health services in hospitals. Based on the results of the performance assessment for 2 years 2021 - 2022, it shows a 5% decrease in health workers at the Intan Medika Lamongan hospital. This study aims to analyze the effect of organizational culture on the performance of health workers at Intan Medika Lamongan Hospital through the Organizational Culture Assessment Instrument (OCAI) approach. The research method is descriptive quantitative and cross sectional approach and data collection techniques through questionnaires. The study population was all health workers using proportionate random sampling method. The number of respondents was 71 health workers with details of 87.3% or 62 women and 12.7%. While based on the profession, the most respondents were nurses with 56.3% and the smallest respondent was the nutrition profession, namely 1.4%. The results showed that the effect of Organizational Culture (variable X) on Performance Appraisal of Health Workers (variable Y) is positive with a significance value of 0.021.